2020
DOI: 10.21273/horttech04664-20
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Field Assay for Pineapple Fruit Acidity

Abstract: The sugar-to-acid ratio of pineapple (Ananas comosus L.) contributes toward giving the fruit its unique flavor. This ratio is an important indicator of both commercial and organoleptic ripeness, and it is useful in determining a harvest date. Citric acid is the major acid in pineapple and usually is determined by titration to a specific pH endpoint, while sugars are determined as total soluble solids by refractometry. Both acid and sugar levels vary with the season in the year-round production cycle. Acid titr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Ogori et al [29] reported a • Brix of 9.32 and TA of 0.84 for their 80P10T10G juice, which differed from our study's same composition formulations. However, the increase in the TSS and TA in pineapple juice may correlate with changes in the citric acid content, which can be influenced by variety, maturity, storage temperature, and post-harvest handling [30,31]. Mean values ± standard deviations followed by different letters within a column indicate significant differences using a Tukey's HSD test at α = 0.05.…”
Section: Total Soluble Solids (Tss) and Titratable Acidity (Ta)mentioning
confidence: 99%
“…Ogori et al [29] reported a • Brix of 9.32 and TA of 0.84 for their 80P10T10G juice, which differed from our study's same composition formulations. However, the increase in the TSS and TA in pineapple juice may correlate with changes in the citric acid content, which can be influenced by variety, maturity, storage temperature, and post-harvest handling [30,31]. Mean values ± standard deviations followed by different letters within a column indicate significant differences using a Tukey's HSD test at α = 0.05.…”
Section: Total Soluble Solids (Tss) and Titratable Acidity (Ta)mentioning
confidence: 99%
“…Ratio is an important measure for pineapple breeding, especially when the objective of the program is development of cultivars for the in natura market, that is, for consumption as fresh fruit. Ratio defines flesh flavor and serves as a useful indicator to determine the time of harvest (Paull et al 2020).…”
Section: Selection Of Genotypes With Superior Crownless Fruit Weight ...mentioning
confidence: 99%
“…Pineapple (Ananas comosus) is a popular tropical fruit that is characterized by its sweet and acidic flavor (Paull et al, 2020). Pineapple juice is a good source of copper, magnesium, vitamin B, potassium, hydroxycinnamic acids, especially manganese and vitamin C .…”
Section: Microbial Safety Of Pineapple Juicementioning
confidence: 99%